Baseline tumor growth rate highlights the heterogeneity of well differentiated gastroenteropancreatic neuroendocrine tumors and predicts for increases in Ki67 index over time. (1st April 2023) - Wang, Stephanie J.; Whitman, Julia; Paciorek, Alan; Le, Bryan Khuong; Nakakura, Eric K.; Behr, Spencer C.; Joseph, Nancy; Zhang, Li; Hope, Thomas A.; Bergsland, Emily K.
Abstract: Refined risk stratification for gastroenteropancreatic neuroendocrine tumors (GEP‐NETs) has the potential to improve comparisons of study populations across clinical trials and facilitate drug development. Tumor growth rate (TGR) is a radiological metric with demonstrated prognostic value in well differentiated grade 1 and 2 (G1–2) GEP‐NETs, but little is known about TGR in G3 NETs. In this retrospective study of 48 patients with advanced G1–3 GEP‐NET, we calculated baseline TGR (TGR0 ) from radiological images of metastases acquired prior to first‐line therapy and evaluated its association with disease characteristics and outcomes. The median pretreatment Ki67 proliferation index for G1–3 tumors combined was 5% (range = 0.1%–52%) and median TGR0 was 4.8%/month (m) (range = 0%–45.9%/m). TGR0 correlated with pretreatment Ki67 across G1–3 pooled and within G3 GEP‐NET. Patients with higher TGR0 (>11.7%/m) tumors, which were primarily G3 pancreatic NETs, exhibited decreased time to first therapy (median, 2.2 vs. 5.3 months; p  = .03) and shorter overall survival (median, 4.1 years vs. not reached; p  = .003). Independent of therapies given, higher TGR0 GEP‐NETs experienced a greater incidence of Ki67 increase (100 vs. 50%; p  = .02) and greater magnitude of Ki67 change (median, 14.0 vs. 0.1%; p  = .04) upon serial biopsy. Importantly, TGR0, but not grade, predicted for future Ki67 increase in this series. Given the heterogeneity of well differentiated GEP‐NETs, future clinical trials may benefit from stratification for TGR0, particularly in G1–2 tumors, in which TGR0 does not correlate with Ki67. TGR0 has the potential to noninvasively identify patients with previously undiagnosed grade progression and those in whom more or less frequent monitoring may be appropriate. Additional research is needed to determine the prognostic and predictive value of TGR0 in larger and more homogeneously treated cohorts, and to ascertain if post‐treatment TGR has value in previously treated patients starting a new line of therapy. Abstract : Baseline tumor growth rate (TGR0 ) a radiologic metric that characterizes tumor kinetics from who contrast‐enhanced scans prior to treatment initiation, has prognostic value in grade 1/2 gastroenteropancreatic neuroendocrine tumors (NETs). This retrospective study extends prior findings to grade 3 NETs and reveals that TGR0 predicts for increases in the ki67 proliferation index over time.